THE EFFECT OF THICKNESS AND SOAKING TIME ON QUALITY OF SMOKED FILLET MACKAREL (Euthynnus affinis) WITH LIQUID SMOKE - Fandi Santoso; Sukirno Mus; N Ira Sari (Jurnal Online Mahasiswa (JOM) Bidang Perikanan dan Ilmu Kelautan, 2015)
This research had been conducted in November 2014 in order to determine the effect of thickness and soaking time for the quality of smoked fillet mackarel with liquid smoke. The quality parameters were the organoleptic, chemical, and microbiology. To achieve these objectives the experimental method was used to perform the smoking mackerel with different thickness and soaking time. Two kind of the fillets thickness were tested (1 and 1,5 cm), then a soaking time (30 and 45 minutes) were applied in the liquid smoke with concentrations of 7% and dried at a temperature of 60ºC for 16 hours. Data were tabulated and analyzed using analysis of variance (Completely Randomized Design/CRD) with factorial 2x2. It was found that smoked mackerel fillets with a thickness of 1,5 cm with the soaking liquid smoke for 45 minutes was the best in the sensory quality. Value of appearance, smell, taste, and texture of smoked mackerel fillets were (7,40), (8,09), (7,53), and (7,45), while the microbiological and chemical values which include the total bacterial colonies, moisture, fat, and pH were (5.6 x 103sel/g), (28.44%), (1.83%), and (5.40 ). The statistical analysis showed that the interaction of the thickness and the soaking time was highly significant (p <0.01) to the value of the fat and also significantly (p <0.05) to the value of the moisture content and the total bacterial colonies, while the value of the pH and the organoleptic were not effected by the treatment interaction of the thickness and the soaking time.Keywords: fillet, thickness, soaking time